Analisis Jaringan 4G untuk Aplikasi Smart Ambulance - Jayati, Ari Endang; Harmini; Budiningrum, Diah Setyati (Emitor: Jurnal Teknik Elektro, 2024)
Intelligent Transport System (ITS) is an intelligent traffic system used for traffic management and engineering. The ITS network uses inter-vehicle telecommunication technology. The city of Semarang is one of the cities that will establish ITS technology. One area that applies technology is health. The telecommunications system applied in the health sector today allows medical staff to treat patients in ambulances before arriving at the hospital. This communication system needs to be supported by a good cellular network so that data can be sent to the server. This study aims to measure QOS (Quality of Service) including the characteristics of delay, packet loss, jitter, and throughput from various cellular providers. The results of data measurements using wireshark software with TIPHON standard guidelines obtained an average value for delay obtained by Provider A with the best result of 86.22 ms. The average value for packet loss obtained from the measurement results from the Penggaron Terminal to the City Hall Bus Stop was obtained by Provider A with the best result of 0.474% d for the City Hall Bus Stop to the Penggaron Terminal obtained by Provider B with the best result of 0.574%. The average value of jitter obtained from the measurement results from the Penggaron Terminal to the City Hall Bus Stop was obtained by Provider B with the best result of 0.42 ms, for the City Hall Bus Stop to the Penggaron Terminal, Provider A was obtained with the best result of 0.57 ms. The average throughput value obtained from the measurement results for Penggaron Terminal to City Hall Bus Stop was obtained by Provider C with the best result of 6631 Kbps, for City Hall Bus Stop to Penggaron Terminal obtained by Provider B with the best result of 6339.5 Kbps. Based on this, knowing the value of delay, packet loss, jitter and throughput is expected to be a consideration for the development of a smart ambulance system in the city of Semarang. There are two measurement points, namely the Penggaron Terminal to the City Hall Bus Stop and the City Hall Bus Stop to the Penggaron Terminal using the Semarang BRT.